Esophageal submucosal dissection under steady pressure automatically controlled endoscopy (SPACE): a randomized preclinical trial - Nakajima, K.; Moon, J. H.; Tsutsui, S.; Miyazaki, Y.; Yamasaki, M.; Yamada, T.; Kato, M.; Yasuda, K.; Sumiyama, K.; Yahagi, N.; Saida, Y.; Kondo, H.; Nishida, T.; Mori, M.; Doki, Y. (Endoscopy, 2012)
Background and study aims: A new overtube system has been developed for steady pressure automatically controlled endoscopy (SPACE) in the gastrointestinal tract. The objectives of this study were to validate the feasibility and safety of SPACE in the esophagus, and to evaluate its potential advantages over conventional (manually insufflating) endoscopy in endoscopic submucosal dissection (ESD).Methods: This was a multicenter preclinical trial using acute porcine models (n = 20). In Experiment 1 (feasibility/safety study), SPACE was attempted in the esophagus with continuous monitoring of cardiopulmonary parameters and intraluminal pressures in the downstream bowel. Different insufflation pressures were tested to optimize the insufflation condition. Each session was video-recorded and scored by blinded reviewers. In Experiment 2 (randomized trial), esophageal ESD was attempted using either SPACE or conventional endoscopy, and results were compared.Results: In Experiment 1, SPACE was performed safely without intraluminal pressure elevation in the downstream bowel. According to video review, SPACE provided more stable, reproducible, and rapid visualization than conventional endoscopy. The insufflation pressure was optimized at 14 mmHg for esophageal SPACE. In Experiment 2, ESD was completed in all animals. The ESD time was significantly shorter with SPACE compared with conventional endoscopy (1326 vs. 1616 seconds; P = 0.009). Responses to questionnaires showed that 94 % – 100 % of participants considered SPACE to provide improved exposure and more uniform tissue tension than conventional endoscopy. Other data were comparable.Conclusions: SPACE is feasible, safe, and potentially effective for complicated endoscopic procedures, such as ESD. SPACE improves and standardizes endoscopic exposure and tissue tension. A clinical study is required to further confirm its safety and clinical effectiveness.